Cryogenic tensile behavior of laser additive manufactured CoCrFeMnNi high entropy alloys - Kim E.S.; Ramkumar K.R.; Karthik G.M.; Jeong S.G.; Ahn S.Y.; Sathiyamoorthi P.; Park H.; Heo Y.-U.; Kim H.S. (My University, 2025)
In the present work the microstructural evolution, tensile properties, and deformation behavior of additively manufactured equiatomic CoCrFeMnNi high entropy alloy (HEA) were investigated at a cryogenic temperature (77 K). Metal additive manufacturing components are known to have exceptional yield strength, without compromising ductility. Here, laser powder bed fusion (LPBF) and direct energy deposition (DED) additive manufacturing processes were chosen as the fabrication techniques and wrought CoCrFeMnNi HEA was also fabricated for comparison. The tensile behaviors at different temperatures (298 K and 77 K) indicated temperature-dependent strength and ductility in all the samples. In particular, the HEA processed by DED exhibited excellent strength and ductility, with exceptional strain hardening, compared to the LPBF and wrought samples at 77 K. Post-tensile microstructures revealed the formation of deformation twinning in addition to dislocation slip as deformation mechanism at 77 K. Our results suggest that cellular structure plays an essential role in yield strength. Moreover, the interactions of the deformation twins and cellular dislocation structures increase strain hardening and help retard plastic instability, thereby improving ductility at 77 K. © 2023 Elsevier B.V.